Neonatal Arterial Ischemic Stroke – A Hospital Based Active Surveillance Study in Germany - Klemme, Mathias; Gerstl, Lucia; Weinberger, Raphael; Olivieri, Martin; Flemmer, Andreas; von Kries, Rüdiger; Felderhoff-Müser, Ursula; Dzietko, Mark (Klinische Pädiatrie, 2017)
Background Neonatal arterial ischemic stroke (NAIS) accounts for substantial long term sequelae in children. The potential effectiveness of neuroprotective therapies needs to be evaluated in appropriate studies with sufficient power.Objective To identify annual number of NAIS cases in Germany potentially eligible for randomized interventional trials.Methods Active surveillance for NAIS in 345 pediatric hospitals with questionnaire based validation of reported cases.Results Incidence of NAIS (7.1/100000 births) was in the range of other population-based studies. To design future clinical trials with anticoagulative or regenerative therapies, it is of major importance to distinguish between cases with or without relevant perinatal pathology. Children without underlying disease or premature birth accounted for 56% of all reported NAIS cases (primary NAIS). In 69% of the primary cases clinical seizures were observed. Although 31% showed other, less pathognomonic symptoms, NAIS was diagnosed. Mean time span between onset of symptoms and diagnosis was 2.9 days. The sensitivity of the initial ultrasound performed in all cases was 69%.Conclusions NAIS is a rare but not negligible morbidity in newborns. Asymptomatic children account for 56% of NAIS in all neonates. In these, not only seizures but also other unexplained symptoms should trigger diagnostic work-up with cUS and cMRI. Negative initial ultrasound results do not exclude NAIS.
Keywords: neonatal stroke; cranial ultrasound; MRI; neonatal arterial ischemic stroke